Optogenetic activation of neocortical neurons in vivo with a sapphire-based micro-scale LED probe - McAlinden, Niall; Gu, Erdan; Dawson, Martin D.; Sakata, Shuzo; Mathieson, Keith (Frontiers in Neural Circuits, 2015)
Optogenetics has proven to be a revolutionary technology in neuroscience and has advanced continuously over the past decade. However, optical stimulation technologies for in vivo need to be developed to match the advances in genetics and biochemistry that have driven this field. In particular, conventional approaches for in vivo optical illumination have a limitation on the achievable spatio-temporal resolution. Here we utilize a sapphire-based microscale gallium nitride light-emitting diode (µLED) probe to activate neocortical neurons in vivo. The probes were designed to contain independently controllable multiple µLEDs, emitting at 450 nm wavelength with an irradiance of up to 2 W/mm2. Monte-Carlo stimulations predicted that optical stimulation using a µLED can modulate neural activity within a localized region. To validate this prediction, we tested this probe in the mouse neocortex that expressed channelrhodopsin-2 (ChR2) and compared the results with optical stimulation through a fiber at the cortical surface. We confirmed that both approaches reliably induced action potentials in cortical neurons and that the µLED probe evoked strong responses in deep neurons. Due to the possibility to integrate many optical stimulation sites onto a single shank, the µLED probe is thus a promising approach to control neurons locally in vivo.